Lesson Plans Alignment with Teaching Performance of Pre-Service Teachers: A Quantitative Study in Micro-Teaching Context - Aryuliva Adnan; Caca Yunisari; Fadilah Habibul Hasna (Ta'dib, 2026)
This quantitative descriptive study examined micro‑teaching performance of 30 pre‑service English teachers and alignment between lesson plan (LP) and teaching performance (TP). Performance was assessed across introduction, main activities, and closure. Descriptive statistics showed moderate‑to‑strong performance in introductions (M = 78.23) and main activities (M = 82.47), but weaker closures (M = 72.10; 23% Excellent). Spearman’s correlation revealed a very weak, non‑significant LP‑TP relationship (rs = 0.151, p = 0.425), indicating aligned plans do not reliably translate into performance. High closure inconsistency (SD = 10.74) partially explains this. Findings imply pre‑service preparation should prioritize rehearsed closure routines. The study contributes empirical evidence on the planning‑enactment gap and identifies lesson closure as a critical target for curriculum improvement in Indonesian pre‑service English teacher education.